Wavelet analysis of movement related EEG - Ibrahim, Muhammad Nasir (2007)
A wavelet is a mathematical function used to divide a given function or continuous-time signal into different scale components. Usually one can assign a frequency range to each scale component. Each scale component can then be studied with a resolution that matches its scale.